The Effect Of Profitability And Solvency On Income Smoothing With Good Corporate Governance As A Moderating Variable At Pt Bank Muamalat Indonesia In 2018-2022 - Andri Seomitra; Aqwa Naser Daulay; Maulida Jam’ah (UNIVED Press, 2024)
This research aims to determine the effect of profitability and solvency on income smoothing with good corporate governance as a moderating variable at PT Bank Muamalat Indonesia in 2018-2022. This type of research is quantitative research with the type of data using secondary data which is collected on the official website of PT Bank Muamalat Indonesia. The data analysis method uses SEM, namely PLS with the SmartPLS program to analyze Good Corporate Governance as a moderating variable which can strengthen or weaken the relationship between the independent variable and the dependent variable. The research results show that profitability has a positive effect on income smoothing, meaning that the higher the level of profitability, the higher the possibility of income smoothing. Solvency has a positive effect on income smoothing, meaning that the higher the level of solvency, the higher the possibility of income smoothing. GCG has a positive effect on income smoothing, meaning that the better corporate governance (GCG), the higher the possibility of income smoothing. GCG is able to moderate the influence of profitability on income smoothing with a positive influence, meaning that GCG is able to strengthen the relationship between profitability and income smoothing. GCG is able to moderate the influence of solvency on income smoothing, meaning that GCG is able to influence the relationship between solvency and income smoothing.